Life Cycle Assessment Optimization of a Shotcrete Tunnel Lining - Štěpánek, Petr; Laníková, Ivana; Venclovský, Jakub (IOP Publishing, 2018)
The proposed contribution describes the formulation of the optimization design of a utility tunnel lining. The objective function is defined as a multicriterial problem and includes economic and environmental aspects associated not only with concrete member production but also with maintenance during utilization (life cycle assessment). The constraining conditions expressed by relations derived from equations of equilibrium (the solution of optimization calculations for a structure with a Winkler foundation using the Finite Element Method), the reliability conditions of a reinforced concrete structure and the continuity of deformations define the range of allowable solutions from the mathematical viewpoint. The thickness of the tunnel lining and areas of the top and bottom reinforcement in cross-sections are optimized

The proposed contribution describes the formulation of the optimization design of a utility tunnel lining. The objective function is defined as a multicriterial problem and includes economic and environmental aspects associated not only with concrete member production but also with maintenance during utilization (life cycle assessment). The constraining conditions expressed by relations derived from equations of equilibrium (the solution of optimization calculations for a structure with a Winkler foundation using the Finite Element Method), the reliability conditions of a reinforced concrete structure and the continuity of deformations define the range of allowable solutions from the mathematical viewpoint. The thickness of the tunnel lining and areas of the top and bottom reinforcement in cross-sections are optimized
Life Cycle Assessment Optimization of a Shotcrete Tunnel Lining
Keywords: optimization; life time assessment; concrete; reinforcement; tunnel lining; optimization; life time assessment; concrete; reinforcement; tunnel lining